2008
DOI: 10.1007/s00436-008-1267-y
|View full text |Cite
|
Sign up to set email alerts
|

Another African disease in Central Europa: Besnoitiosis of cattle. I. Light and electron microscopical study

Abstract: The paper reports the first detection of besnoitiosis of cattle in Germany. Just 2 years after the first appearance of the African Bluetongue disease (BTD) of cattle in Central Europe, another African agent of disease has arrived in Germany. While it was proven that the BTD virus was transmitted (after its first appearance) by endemic midges of the genus Culicoides (C. obsoletus, C. pulicaris), nothing is known, how the infectious stages of Besnoitia besnoiti-a member of the so-called cyst-forming coccidia-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…Although the transmission cycle of B. tarandi is not fully understood, it is believed that it cycles through a predatorprey system with a carnivore as the definitive host (Dubey et al, 2004). However, wild ruminants and rodents should not be ruled out as potential reservoirs (Castillo et al, 2009;Mehlhorn et al, 2009). Biting or bloodsucking arthropods also may be important vectors of B. tarandi (Glover et al, 1990), but unlike bovine besnoitiosis (Bigalke, 1968), this has not been scientifically demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the transmission cycle of B. tarandi is not fully understood, it is believed that it cycles through a predatorprey system with a carnivore as the definitive host (Dubey et al, 2004). However, wild ruminants and rodents should not be ruled out as potential reservoirs (Castillo et al, 2009;Mehlhorn et al, 2009). Biting or bloodsucking arthropods also may be important vectors of B. tarandi (Glover et al, 1990), but unlike bovine besnoitiosis (Bigalke, 1968), this has not been scientifically demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…13,35,37 However, in light microscopic pictures, the ICW can be seen as a blue 37 or slightly eosinophilic layer. 35 Perhaps this layer was interpreted as artifact, occurring after processing of tissues for histological examination.…”
mentioning
confidence: 99%
“…The collagenous nature of the OCW 13,35,37 resulted in a blue staining with Masson's trichrome stain and a red staining with orange-colored birefringence in polarized light in picrosirius red/Alcian blue stain, with the latter suggesting that the OCW is made up of collagen type I fibers.…”
mentioning
confidence: 99%
“…The present experimental study found skin thickening and hair loss to be features of the chronic phase, as previously reported in relation to various naturally occurring besnoitioses, 9,13,19 whereas resolution of the skin lesions was similar to that in some other Besnoitia infections. 16 The appearance of cysts at about 35 days after infection is somewhat earlier than that reported in native goats in Kenya, 21 with observation of Besnoitia cysts 56 and 60 days after bradyzoite inoculation. That experiment described cysts for a short period in some organs after infection but not the longer-term progressive changes in cysts and the associated tissue reactions during cyst degeneration, as shown in this study.…”
Section: Discussionmentioning
confidence: 75%